KONTRIBUSI PAJAK BUMI DAN BANGUNAN (PBB) DALAM MENINGKATKAN PENERIMAAN PAJAK DAERAH - Hesti Pratiwi; Muhaimin Muhaimin; Wa Ode Rayyani (Universitas Muhammadiyah Makassar, 2020)
This study aims to answer the problems regarding the contribution of the United Nations in increasing the regional tax revenue of the city of Makassar and knowing taxpayer compliance in making payments on Land and Building Taxes so as to obtain the realization of land and building tax revenues. This research is a kind of descriptive quantitative research. The data of this study include primary and secondary data. The results of the study showed that the number of taxpayers was greatly increased but taxpayers did not have awareness and compliance with their obligations. This does not have a positive impact in increasing local tax revenue so that the acquisition of percentages and targets and realization of land and building tax revenues experience instability in achieving the targets set by the government. In 2017 and 2018 the decline in some sub-districts has decreased revenue realization caused by by economic factors